Case study of a mesospheric wall event over Ferraz station, Antarctica (62° S) - J. V. Bageston (Annales Geophysicae, 2011)
On 16–17 July 2007 during an observational campaign at Comandante Ferraz Antarctic Station (62° S, 58° W), a mesospheric wall was observed with an airglow all-sky imager. The wave appeared like an extensive dark region in the all-sky airglow images, with a large depletion in the OH emission. Simultaneous mesospheric winds measured with a MF radar at Rothera station and temperature profiles from SABER instrument, on board of TIMED satellite, were used to obtain the propagation condition of the wave. Wind measurements during four days, around the time of observation of the wave, are presented in order to discuss the type and consistence of the duct in which this wave was propagating. By using wavelet analysis and tidal amplitude components we found that 12 and 8 h components were the most important periodicities around the time interval of the wave observation. A collocated imaging spectrometer, for mesospheric temperature measurements, has been operated simultaneously with the all-sky imager. Direct effects of the mesospheric front have been seen in the spectrometric measurements, showing an abrupt decrease in both OH intensity and rotational temperature when the wave front passes overhead. The main contribution of the present work is the investigation of the type of duct in which the wall event was propagating. We found evidences for a thermal duct structure to support the mesospheric wall propagation. This result was obtained by two types of analysis: (a) the tidal components analysis and winds filtering (harmonic analysis), and (b) comparison between the terms of the m2 dispersion relation.